Analysis of Financial Performance of Indonesian Banking Companies Using the Z-Score Model - Mira, Mira; Badollahi, Ismail; Akbar, Akbar (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2024)
This research aims to find out how to analyze the financial performance of banking companies in Indonesia using the Z-Score model. This research uses a descriptive quantitative approach and uses the Z-Score model to assess banking performance. The data processing stages begin with collecting financial report data according to the Z-Score model indicators, calculating each indicator item, formulating the results according to the Z-Score model, analyzing them and drawing research conclusions. The financial report data taken is 3 years (2020-2022) which is time series data. The results of this research show that the overall financial performance of Indonesian banking seen from the Z-Score Model shows that the majority are in the bad category and 4 banks are in the healthy category, namely AMAR, ARTO, BTPS and PNBS. AMAR is categorized as healthy for 2022, ARTO 2021, BTPS for 2020-2022 is consistently considered healthy and PNBS is also considered healthy for 2020-2022. This shows that financial supervision needs to be improved and this information provides a warning to all banks that must focus more on efforts to improve their respective financial performance to increase existing ratios.